2010
DOI: 10.1007/s10439-010-9917-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intermittent Static Biaxial Tensile Strains on Tissue Engineered Cartilage

Abstract: Mechanical stimulation of engineered cartilage constructs is a commonly applied method used to accelerate tissue formation and improve the mechanical properties of the developed tissue. While the effects of compression and shear have been widely studied, the effect of tension has received relatively little attention. As articular cartilage in vivo is subjected to a degree of static tension (pre-tension) even in the absence of externally applied loads, the purpose of this study was to investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Intermittent loading regimes have significant effect on ECM production. 41,50 In particular, Nicodemus and Bryant 41 showed that loading and the timing of when loading is applied can dramatically influence the anabolic and catabolic activities of chondrocytes in polyethylene glycol gels. A delayed loading regime has less effect on stimulating anabolic and catabolic gene expression in comparison to using an immediate application of an intermittent loading regime.…”
Section: Fig 5 Viability Assessment Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Intermittent loading regimes have significant effect on ECM production. 41,50 In particular, Nicodemus and Bryant 41 showed that loading and the timing of when loading is applied can dramatically influence the anabolic and catabolic activities of chondrocytes in polyethylene glycol gels. A delayed loading regime has less effect on stimulating anabolic and catabolic gene expression in comparison to using an immediate application of an intermittent loading regime.…”
Section: Fig 5 Viability Assessment Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…On the other hand, it was suggested cyclic tension activates the hypertrophic pathway and increases the expression of markers typically associated with chondrocytes undergoing terminal differentiation to hypertrophic chondrocytes (eg, collagen X) [99]. Because there is evidence that articular cartilage in vivo is under a degree of static pretension, the effect of intermittent static biaxial tensile strains on cartilaginous constructs was studied [24]. Average magnitudes of 3.8% radial and 2.1% circumferential tensile strains for 30 minutes were identified as leading to the greatest increase in proteoglycan content.…”
Section: Tensionmentioning
confidence: 99%
“…For instance, the mechanical compression of primary chondrocytes affects ATP release, 3 ion channel formation, 4 activates transcription factors such as NF Kβ 5 and can activate kinases such as MAP kinase, 6 focal adhesion kinase, 7 and ERK, 8 as well as Interleukin-1 signaling. 9 More long term, mechanical loading can also alter the expression of collagen [10][11][12][13][14][15][16] and enzymes 7,17 involved in tissue remodeling. Typical frequencies encountered in cell loading in these cases are on the order of 1-10 Hz.…”
Section: Introductionmentioning
confidence: 99%